Prevalence of emotional burnout among dietitians and nutritionists: a systematic review, meta-analysis, meta-regression, and a call for action - Omar A. Alhaj; Nour A. Elsahoryi; Feten Fekih-Romdhane; Manar Wishah; Dima H. Sweidan; Waqar Husain; Ammar Achraf; Khaled Trabelsi; James R. Hebert; Haitham Jahrami (BMC Psychology)
Abstract Background and objectives Despite anecdotal evidence pointing to the high prevalence of job stress and burnout among dietitians and nutritionists, few studies have been conducted on this topic. Moreover, most studies are from Western countries. The objective of the current study, based on systematic review, meta-analysis, and meta-regression, is aimed to provide systematically graded evidence to assess the prevalence of emotional burnout among dietitians and nutritionists across age, sex, and cultural backgrounds. Methods Two reviewers independently conducted a systematic search from 1 January 2000, to 1 April 2024 and was later updated to 15 November 2024, across seven databases: EBSCOhost Research Platform, EMBASE, PubMed/MEDLINE, ProQuest, ScienceDirect, Scopus, and Web of Science. The DerSimonian-Laird method was utilized to pool the data in this meta-analysis. Data from a total of 12,166 dietitians and nutritionists were extracted from 16 datasets (published in twelve research reports) covering a period of approximately 25 years. We measured the pooled prevalence of global burnout syndrome and its individual symptoms among dietitians and nutritionists. Subgroup meta-analyses were also conducted to identify a comprehensive set of moderators, including participants’ age and sex. Results The prevalence of global burnout syndrome in dietitians and nutritionists (K = 10, N = 10,081) showed an overall prevalence rate of 40.43% [23.69; 59.74], I² = 99.3%, τ [95% CI] = 1.18 [0.84; 1.97], τ² [95% CI] = 1.38 [0.71; 3.89], H [95% CI] = 12.68 [11.70; 13.74]. The prevalence of burnout dimensions/individual symptoms in dietitians and nutritionists (K = 2, N = 695) is summarized as follows: emotional exhaustion (EE) at 26.11% [15.14; 41.17], I² = 84.0%, τ = 0.21, τ² = 0.46, Q = 6.25, p < 0.001; depersonalization (DP) at 6.59% [1.08; 31.22], I² = 95.0%, τ = 1.72, τ² = 1.31, Q = 20.18, p < 0.001; and personal accomplishment (PA) at 59.29% [39.81; 76.23], I² = 89.3%, τ = 0.29, τ² = 0.54, Q = 9.36, p < 0.001. Meta-regression showed no difference by age or sex, p = 0.80, and p = 0.20, respectively. Conclusion This meta-analysis revealed that the prevalence of burnout among dietitians and nutritionists is as high as in other medical professionals. Furthermore, age and sex were not significantly associated with emotional burnout among dietitians and nutritionists. This study provides the impetus for policy changes to improve dietitians’ and nutritionists’ working conditions, as well as the overall quality of nutrition care.